An Adaptive Algorithm for Image Encryption: Pseudo Random Generator with Crossover of Genetic Algorithm - Baqer Taher, Hazeem (University of Thi-Qar Journal of Science, 2011)
In this paper proposed an adaptive approach for image encryption. We used linearcongruential random number generators to produce the pseudo random sequence. The inputimage is encrypted using pseudo random with crossover of genetic algorithm. This newencryption method can be used to encrypt an image with high secure, fast and lossless. Itcan be used to send the encrypted image through network and secure data storage (such asimportant documents). To validate our work, several experiments are executed on a numberof different features (details) images. The proposed method reduces the weakness area in theencryption method and increasing the randomness of the encrypted image